Sharing Skills and Needs between Providers and Users of Climate Information to Create Climate Services: Lessons from the Northern Adriatic Case Study - Valentina Giannini; Alessio Bellucci; Silvia Torresan (Fondazione Eni Enrico Mattei (FEEM), 2016)
The need to cope with the expected impacts of climate change on socio-ecological systems calls for a closer dialogue between climate scientists and the community of climate information users (e.g. decision makers belonging to public institutions). We describe an interactive process designed to bridge this gap by establishing a two-way communication, based on mutual learning. We analyse the need of climate information for the integrated assessment of climate change impacts on the coastal zone of the Northern Adriatic Sea, which is considered to be particularly vulnerable to several climate-related phenomena, e.g. heavy rainfall events, pluvial flood, and sea-level rise, causing potentially high damages to coastal eco-systems and urban areas (e.g. acqua alta in the Venice Lagoon). A participatory process is designed engaging representatives from both the scientific and local stakeholders communities, and facilitated by a boundary organization, embodied by the Euro-Mediterranean Center on Climate Change.
Keywords: O1; Q2; R5; 330; Decision Making; Climate Products; Climate Services; Risk Assessment; Northern Adriatic; Participatory Process; CLIM-RUN